Bargaining in standing committees - Vincent Anesi; Daniel J. Seidmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
Committee voting has mostly been investigated from the perspective of the standard Baron-Ferejohn model of bargaining over the division of a pie, in which bargaining ends as soon as the committee reaches an agreement. In standing committees, however, existing agreements can be amended. This paper studies an extension of the Baron-Ferejohn framework to a model with an evolving default that reflects this important feature of policymaking in standing committees: In each of an infinite number of periods, the ongoing default can be amended to a new policy (which in turn determines the default for the next period). The model provides a number of quite different predictions. In particular: (i) Substantial shares of the pie are wasted each period and the size principle fails in some pure strategy Markov perfect equilibria of non-unanimity games with patient enough players; and (ii) All Markov perfect equilibria are Pareto inefficient when discount factors are heterogenous. However, there is a unique equilibrium outcome in unanimity standing committee games, which coincides with the unique equilibrium outcome of the corresponding Baron-Ferejohn framework.
Keywords: C73; C78; D71; D72; 330; legislative bargaining; endogenous default; efficiency; pork barrel